Application of Artificial Intelligence in Educational Contexts for Teaching and Learning (International Journal of Innovative Research in Computer Science & Technology, 2022)
Innovative educational technology have  transformed teaching and learning techniques. Higher  education has recently begun to incorporate new technology  as artificial intelligence advances. The purpose of this  conceptual review article is to look into the rise of artificial  intelligence in education teaching and learning. It  investigates the educational implications of emerging  technology on how schools educate and how students learn.  The goal of this research is to forecast the role of artificial  intelligence in the future of education in the globe. Artificial  intelligence approaches that are used effectively are seen as  a way to improve the quality of teaching and learning The  difficulties of incorporating artificial intelligence in  educational institutions, on the other hand, are addressed.  Furthermore, the difficulties encountered artificial  intelligence adoption by students in terms of student  assistance, teaching, and learning The topics of governance  and administration are explored. This article provides a short  review of the most current research findings. research to  illustrate how artificial intelligence may be used in  educational settings The There are some suggestions for  further study and consequences.
Keywords: Artificial Intelligence; Educational; Learning; Teaching; Technologies